The aphid fauna (Hemiptera, Sternorrhyncha, Aphidomorpha) of Murmansk province (Russia), with description of Aphis khrulevi sp. nov. and Dysaphis karyakini sp. nov. and males of Chaitophorus nigricantis Pintera, 1987 - Stekolshchikov, Andrey V.; Buga, Sergey V. (Zootaxa, 2018)
An updated aphid (Hemiptera, Aphidomorpha) check-list of Murmansk province (European Russia) is presented, it includes 162 species. Chaitophorus nigricantis Pintera, 1987, Schizaphis nigerrima (Hille Ris Lambers), Hyperomyzus (Neonasonovia) zirnitsi Hille Ris Lambers, Nasonovia (Kakimia) vannesii Stenseth, Plocamaphis flocculosa goernitzi Börner and Schizaphis graminum gigjai Stroyan are recorded for the first time from Russia. Both apterous and alate males of Chaitophorus nigricantis nigricantis Pintera are described. Two new aphid species are described: Aphis khrulevi sp. nov. from fundatrices and apterous viviparous females, living on Veronica longifolia and Dysaphis karyakini sp. nov. from apterous and alate viviparous females, oviparous females and males, living on Cenolophium denudatum. Comments about the distribution and biology of aphids in this Northern part of Europe, and on the completeness of the list are given.